THE MESSAGE OF THE CASTAWAY: ORPHIC THEMES IN THE POETRY OF KRZYSZTOF KARASEK - Nowaczewski, Artur (Colloquia Litteraria, 2019)
Although Krzystof Karasek counts among the most outstanding representatives of the Nowa Fala (New Wave) generation, his poems have not been subject to detailed analysis so far. The author attempts to highlight the meaning of the Orphic threads in Krzysztof Karasek’s poetry written after 1989. For more than twenty years Karasek’s poems have been tied to each other by a suggestive figure of a hero named by the poet a ‘castaway’. This castaway’s characteristics include distance to himself and lack of delusion about the condition of the world after personal and cultural collapse. Still, it also includes great appraisal of life. The poet, defining the figure of the castaway, calls in a number of castaway figures, characters after catastrophe, among which one can find the mythical Orpheus. The article addresses the originality of Karasek’s idea with regard to his polemical texts which engaged with Zbigniew Herbert’s and Julian Kornhauser’s works.